An apple a day? Adult food stamp eligibility and health care utilization among immigrants - Chloe N. East; Andrew Friedson (W.E. Upjohn Institute for Employment Research, 2018)
In this study, we document the effect of food stamp access on adult health care utilization. While the Food Stamp Program provides one of the largest safety nets in the United States today, the universal nature of the program across geographic areas and over time limits the potential for quasi-experimental analysis. To circumvent this, we use variation in documented immigrants' eligibility for food stamps across states and over time due to welfare reform in 1996. Our estimates indicate that access to food stamps reduced physician visits. Additionally, we find that for single women, food stamps increased the affordability of specialty health care. These findings have important implications for cost-benefit analyses of the Food Stamp Program, as reductions in health care utilization because of food stamps may offset some of the program's impact on the overall government budget owing to the existence of government-provided health insurance programs such as Medicaid.
Keywords: H51; H53; H75; I11; I18; Q18; 330; Food stamps; immigrants; health care